Inovatif dan Ramah Lingkungan: Implementasi Program CSR Melalui Kegiatan Budidaya Ikan - Abdul Aziz; Afry Rakhmadany; Muhammad Rezky Pratama (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2021)
Indonesia is very rich in fishery potential. The potential that exists makes fish farming propagate in urban and rural areas which in fact are far from the waters (sea). However, the performance problem of fish farming in the terrestrial environment is one of the inhibiting factors for the development of fish production in Indonesia. PT. Pertamina (PERSERO) Fuel Terminal Rewulu is one of the agents who embrace the community to open up opportunities for environmentally friendly innovations in fish farming in the terrestrial environment. This opportunity was used by the community to create an empowerment program with the name NOT MAIN. The background of these problems and ideas has attracted researchers to describe the implementation of CSR through community empowerment based on innovative and environmentally friendly independent fish farming. This study uses a qualitative method which is presented descriptively. The object of this research is the NOT MAIN program. The subjects in this study were the CDO and the administrators of the NOT MAIN program. Informants were determined by purposive sampling technique. In terms of data collection techniques, it is done by interview, observation, and documentation. The data analysis technique used the Miles and Hubermen model. Next is a test of the validity of the data which is done by using triangulation of sources and methods. The results obtained from this research are that the program is implemented with a bottom-up approach which is then carried out within the scope of community empowerment. This program also produces environmentally friendly technological innovations, namely MBG technology based on IoT (banoo sensor), the use of solar cells (DC systems), and modified RAS (Recirculating Aquaculture System).